Controlling a Quadcopter with Static Loads and Dynamic Wind Disturbances using a Fuzzy Inference System - Azka, Aida; Santoso, Ari; Agustinah, Trihastuti (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
Maneuverability, hover, and simple mechanical design are the advantages of quadcopters. However, because quadcopters are smaller and lighter, they are more susceptible to wind than manned aircraft. The winds that cause air accidents are divided into several categories, namely downburst, turbulent wind, wind shear, and wind vortices. Disturbances and uncertainties, such as wind gusts, can result in difficulties in executing a mission on an accurate flight path. Quadcopter resilience is an important topic for UAV. Especially if the quadcopter is in terrain that is difficult for humans to reach. Hence, the system is susceptible and experiences reduced stability. Controlling a quadcopter with a cube-shaped static load to withstand turbulent wind gusts in this research uses robust Fuzzy Inference System control and trajectory control using LQR with Command-Generator Tracking. The results achieved through fuzzy control can fortify the quadcopter against half of the overall turbulent wind gusts with an RMSE of 0.0546. In contrast with the LQR-CGT control, which still exhibits an RMSE of 0.0795.